Role of Women in the Sanitation Promotion and Management (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women are often in charge of cleaning and, in many instances, of disposing of human waste. It is especially important to maintain good sanitation during menstruation, pregnancy, and the postpartum period, when dehydration from toilet avoidance is a serious health risk. Women are particularly sensitive to the concerns about safety and privacy raised by the need for cleanliness. In dozens of nations, including Fiji, India, Brazil, Sri Lanka, the Philippines, Kenya, Ethiopia, and South Africa, widespread violence against women in connection to sanitation usage has been widely documented. Lastly, programmes and initiatives meant to address sustainability in sanitation have been hampered by men and women not being involved enough. Improved sanitation services provide significant socioeconomic advantages, such as increased productivity (owing to less time spent on health and caregiving costs), safety, better health, transparency, good governance, and empowerment. In terms of rights to resources and services, gender mainstreaming may provide women the authority to make strategic decisions, which can increase social capital, education, and the health and productivity of the population.